Between the Patient and Politics – A Ready-to-Use Simulation for Human Service Practitioners. (December 2017) - Mallinson, Daniel J.; O'Hanlon, Erin
Background. Caregivers in human services fields operate within a space between their clients and the larger social forces that shape clients' lives. Empathetic practitioners should learn to identify both personal circumstances and larger systemic forces (e.g., economic inequality) beyond their control that influence patients' circumstances. Aim. This article presents a noveltwo-phase simulation that can be beneficial for increasing empathy and policy knowledge among pre-practitioners in a variety of human service fields. Method. We use a mixed-method design to evaluate the impact of a pilot study (n=9) of the simulation. First, pre-, mid-, and post-event surveys are used in conjunction with t-tests to determine changes in overall empathy and knowledge. Second, we use feedback from the first-phase debriefing and end-of-program focus groups to identify emergent themes. Learnersrole play a state legislator or interest group and must develop legislation to address shortages in physicians and nurses. Result. We found evidence of increased knowledge of the policymaking process and understanding of how politics relates to individualhealthcare access challenges. Evidence of gains in empathy were not apparent from the quantitative measures, but were expressed in participant debriefing. Conclusion. The framework presented is flexible enough to adapt and be implemented for a variety of policy problems across a diverse array of human service fields. It shows promise in raising knowledge and potentially empathy.